Clinical Toxicities of Histone Deacetylase Inhibitors - Richard L. Piekarz; John J. Wright; Susan E. Bates; Srividya Subramanian; Igor Espinoza-Delgado (MDPI AG, 2010)
The HDAC inhibitors are a new family of antineoplastic agents. Since the entry of these agents into our therapeutic armamentarium, there has been increasing interest in their use. Although this family comprises chemical compounds from unrelated chemical classes that have different HDAC isoform specificities, they surprisingly have very similar toxicity profiles. In contrast, the observed toxicity profile is somewhat different from that of traditional cytotoxic chemotherapeutic agents and from other epigenetic agents. While some of the side effects may be familiar to the oncologist, others are less commonly seen. As some patients remain on therapy for a prolonged period of time, the long-term sequelae need to be characterized. In addition, since preclinical models suggest promising activity when used in combination with other antineoplastic agents, combination trials are being pursued. It will thus be important to distinguish the relative toxicity attributed to these agents and be alert to the exacerbation of toxicities observed in single agent studies. Notably, few of the agents in this class have completed phase 2 testing. Consequently, more clinical experience is needed to determine the relative frequency of the observed side effects, and to identify and develop approaches to mitigate potential clinical sequelae.